L'Intervention française au Mexique vue par les principaux journaux canadiens-français du Québec, 1861--1867 - Larrinaga, Jose Antonio de (University of Ottawa (Canada), 1976)
Abstract not available.
Keywords: History, Canadian.; History, Latin American.; Journalism.